Development of a Test for the Real-time Fluorescence RNA Targeted Isothermal Amplification to Quickly Identify Cronobacter Species in Powdered Infant Formula - Ning Ding; Xiaona Tang; Fang Chen; Jiaqi Liang; Li Ling; Song Cheng; Lidan Ma; Yan Lu; Muyun Yuan; Jingwen Liu; Qing Liu; Wenrui Chen; et al. (Journal of Food Protection)
Foodborne bacteria such as Cronobacter are opportunistic and have been connected to potentially fatal infections. The current work created a fast and sensitive RNA targeting amplification and detection system for Cronobacter spp., including enrichment, RNA isolation, and detection by real-time RNA isothermal amplification, capable of detecting viable Cronobacter spp. in powdered infant formula (PIF) and other food products. Total RNA was extracted to optimize Simultaneous Amplification and Testing (SAT) reaction conditions including concentrations of primers, molecular beacon, Mg2+, dNTP, and NTP. The optimized SAT assay targeting 16s/23s rRNA was used to demonstrate the specificity, sensitivity of the detection assay. Seven Cronobacter sakazakii strains and 24 control strains were examined in comparison to that of real-time PCR (SN/T 1632.3) and ISO 22964. The SAT assay showed sensitivity with a detection limit of 2 log10 CFU/ml without preenrichment, 2 log CFU/10 ml with 4 h enrichment, and 2 log CFU/1,000 ml with 7 h preenrichment (The sensitivity of real-time PCR are 3 log CFU/ml without preenrichment, log CFU/ml with 4 h preenrichment, and 2 log CFU/10 ml with 8 h preenrichment) The newly developed assay could provide results in 4 h including enrichment, which has been significantly shortened compare with real−time PCR method with overnight enrichment. Moreover, the SAT assay did not give false positive results when detecting dead C. sakazakii (7-2 log CFU/ml). In contrast, the real-time PCR assay exhibited a detection limit equivalent to that for detecting viable bacteria. The developed SAT assay, combined with enrichment, provides a rapid, sensitive, and simple approach, and has great potential in the detection of Cronobacter species in baby formula and other food goods.